Pemanfaatan GeoGebra dalam Pembelajaran Matematika di Sekolah Menengah Pertama - Rudihastuti Rudihastuti (Action Research Journal, 2022)
In this digital era, the use of computer programs in learning mathematics is a necessity. One of the computer programs that can be used in learning mathematics is GeoGebra. GeoGebra is a dynamic program with various facilities that can be used as a medium for learning mathematics to demonstrate or visualize mathematical concepts and as a tool for constructing mathematical concepts. This article presents a description of the GeoGebra program along with examples of the application of GeoGebra as a medium for learning mathematics, especially at the junior high school level.